New classification of liver biopsy assessment for fibrosis in chronic hepatitis B patients before and after treatment. Issue 5 (22nd March 2017) - Sun, Yameng; Zhou, Jialing; Wang, Lin; Wu, Xiaoning; Chen, Yongpeng; Piao, Hongxin; Lu, Lungen; Jiang, Wei; Xu, Youqing; Feng, Bo; Nan, Yuemin; Xie, Wen; et al.
Abstract : Liver fibrosis is the net result of dynamic changes between fibrogenesis and fibrolysis. Evidence has shown that antiviral therapy can reverse liver fibrosis or even early cirrhosis caused by hepatitis B virus. However, current evaluation systems mainly focus on the severity of, but not the dynamic changes in, fibrosis. Here, we propose a new classification to evaluate the dynamic changes in the quality of fibrosis, namely: predominantly progressive (thick/broad/loose/pale septa with inflammation); predominately regressive (delicate/thin/dense/splitting septa); and indeterminate, which displayed an overall balance between progressive and regressive scarring. Then, we used this classification to evaluate 71 paired liver biopsies of chronic hepatitis B patients before and after entecavir‐based therapy for 78 weeks. Progressive, indeterminate, and regressive were observed in 58%, 29%, and 13% of patients before treatment versus in 11%, 11%, and 78% after treatment. Of the 55 patients who showed predominantly regressive changes on posttreatment liver biopsy, 29 cases (53%) had fibrosis improvement of at least one Ishak stage, and, more interestingly, 25 cases (45%) had significant improvement in terms of Laennec substage, collagen percentage area, and liver stiffness despite remaining in the same Ishak stage. Conclusion : This new classification highlights the importance of assessing and identifying the dynamic changes in the quality of fibrosis, especially relevant in the era of antiviral therapy.(Hepatology 2017;65:1438‐1450)